Does preoperative iodide treatment for thyrotoxicosis bring about involution? - Wilkin, T J (1977)
It is generally believed that preoperative iodide decreases the hyperplasia of the toxic thyroid gland. Histometric studies of glands from thyrotoxic patients pretreated with propranolol alone compared with those from patients pretreated with propranolol and iodide failed to confirm this. Although histological appearances and volume percentage measurement of component tissues suggested that the glandular epithelium had involuted after iodine treatment, measurement of their absolute mass indicated that the mean mass of epithelium was the same in both groups and that involution had not occurred. We conclude that considerable confusion in the thyroid literature has arisen through incorrect use of the term involution.